2017
DOI: 10.1007/s10884-017-9573-7
|View full text |Cite
|
Sign up to set email alerts
|

Stationary Solutions and Connecting Orbits for p-Laplace Equation

Abstract: We deal with one dimensional p-Laplace equation of the formunder Dirichlet boundary condition, where p > 2 and f :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is known (see e.g. [16,Th. 3.5]) that, for any u 0 ∈ X , any integral solution of (5.11) has the following properties…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known (see e.g. [16,Th. 3.5]) that, for any u 0 ∈ X , any integral solution of (5.11) has the following properties…”
Section: 2mentioning
confidence: 99%
“…It is well known that A L 2 is m-accretive (see e.g. [16,Lem. 3.4]) and clearly the part of A L 2 in X is equal to A.…”
Section: 2mentioning
confidence: 99%
“…In addition, the global dynamics of the Swift-Hohenberg model has been uncovered using a Morse decomposition based approach in [17], and the existence of periodic orbits for the ill-posed Boussinesq equation was established in [7,15]. Finally, the existence of a heteroclinic orbit between the trivial and a nontrivial stationary state has been established for the one-dimensional p-Laplace equation in [66]. Also, private communication revealed that Zgliczyński could verify the existence of a heteroclinic connection in the Kuramoto-Sivashinsky equation using similar techniques in the recent work in progress [64].…”
Section: Introductionmentioning
confidence: 99%